1974
DOI: 10.1128/jb.119.1.62-69.1974
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Replication Gap Closure in Escherichia coli by Near-Ultraviolet Light Photoproducts of l -Tryptophan

Abstract: Near-ultraviolet photoproducts of L-tryptophan (TP) differentially inhibited deoxyribonucleic acid (DNA) replication in wild-type cells and uvrA, polAl, and recA recB double mutants of Escherichia coli. Wild-type cells labeled in their DNA with [3H]thymidine in the presence of TP produced small pieces of DNA (7 x 106 daltons), which corresponded in size to late replicative intermediates of discontinuous DNA synthesis. Moreover, when TP was present, it took five times longer to chase the low-molecular-weight DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…They proposed that in the absence of ligase activity cells were unable to rejoin DNA fragments produced during normal DNA replication which, in turn, allowed endonucleases to degrade DNA leading to cell death. Their hypothesis is not necessarily incompatible with ours because one reported effect of peroxide is to inhibit the repair of DNA strand breaks (Yoakum et al 1974).…”
Section: Discussionmentioning
confidence: 52%
“…They proposed that in the absence of ligase activity cells were unable to rejoin DNA fragments produced during normal DNA replication which, in turn, allowed endonucleases to degrade DNA leading to cell death. Their hypothesis is not necessarily incompatible with ours because one reported effect of peroxide is to inhibit the repair of DNA strand breaks (Yoakum et al 1974).…”
Section: Discussionmentioning
confidence: 52%
“…To determine the reason for the genetic specificity of TP toxicity, we conducted experiments to test the effects of TP on deoxyribonucleic (DNA) metabolism. These studies demonstrated that TP blocks a step(s) required for the iapid closure of replication gaps (21) which occur during discontinuous semiconservate DNA replication (7). In addition, we found that TP inhibits one class of X-ray repair, without apparent blockage of other X-ray repair processes.…”
mentioning
confidence: 50%
“…TP inhibits type III repair of X-ray-induced SS breaks without blocking type II repair of DNA SS breaks (20). Since TP blocks processes of DNA metabolism involved in the rejoining of DNA intermediates of repair and replication, we concluded that the dark toxicity of L-tryptophan photoproduct is probably a biological expression of the effect of TP on DNA metabolism (21).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In Escherichia coli and Salmonella typhimurium, DNA is injured by hydrogen peroxide and some DNA repair-deficient strains are more sensitive to hydrogen peroxide than DNA repair-proficient strains (1,10,18,19,20). It has not been established whether these differences in sensitivity to hydrogen peroxide result from the various levels in the cell of the protecting enzymes catalase, peroxidase, or superoxide dismutase.…”
mentioning
confidence: 99%